How spending decisions shape happiness in everyday life - Stenlund, Säde; Guo, Yingchi; Rights, Jason; Dwyer, Ryan; Dunn, Elizabeth (Nature, 2025)
This study examines the emotional consequences of spending choices in everyday life across a diverse multinational sample. Based on a dataset of 200 participants across 7 countries who received $10,000 USD, we analyzed how happy they felt from different types of purchases made with that money. Participants derived high levels of happiness from some types of purchases that have been examined in past research (e.g., buying experiences), but also from other purchases (e.g., education) that have not been the focus of previous work. We found some evidence that the emotional benefits of spending choices varied depending on whether participants lived in higher vs. lower-income countries; specifically, we found differences in the benefits of spending on gifts, housing, debt, and time-saving services. Around the world, people who spent money in ways that made them happy experienced greater improvements in overall subjective well-being 3 and 6 months later.